(untitled) (Research, Society and Development, 2024)
The objective of this article is to report the clinical case of a 38-year-old patient with a suspected diagnosis and intraoperative confirmation for the presentation of Valentino syndrome, emphasizing the importance of differential diagnosis in clinical practice with symptoms of acute appendicitis, taking into account adequate interrogation and construction of important background information to rule out this type of pathology. The patient experienced typical clinical manifestations of acute appendicitis, however, with a history of alcohol consumption prior to the onset of pain, as well as the continuous evolution for a prolonged period of 10 days, which indicates a presentation of peptic ulcer vs acute appendicitis, Additionally, the exploratory laparotomy revealed a perforated gastric ulcer and when performing the appendectomy, a phase 1 appendix was identified. The treatment method used was appendectomy and repair. Of omentum patch ulcer. A successful postoperative recovery was obtained without complications. All results highlight the importance of a comprehensive approach and complex imaging examination, such as CT, in the diagnosis of acute abdomen with atypical symptoms. The need for a comprehensive approach in the anamnesis and description of history, as well as early surgical treatment, is thus identified.